CORRELATION BETWEEN NECK CIRCUMFERENCE AND SKINFOLD THICKNESS TOWARDS BODY MASS INDEX ON THE STUDENTS OF MEDICAL FACULTY ISLAMIC UNIVERSITY OF NORTH SUMATRA - Pane, Aulia Rahmadani Putri; Ismail, Wan Muhammad (JURNAL KESMAS DAN GIZI (JKG), 2023)
Obesity is a global epidemic that must be addressed immediately because it can trigger various degenerative diseases. Early prevention by using screening through anthropometric measurements such as body mass index, neck circumference, and skinfold thickness is needed in assessing nutritional status. The research method is descriptive-analytic with a cross-sectional approach. The research subjects consisted of 77 students of the Faculty of Medicine, Islamic University of North Sumatra who were taken using the consecutive sampling method. Research results based on male and female gender and nutritional status category, the average BMI for men was 25.0 kg/m2 (Obesity I), and for women was 24.6 kg/m2 (Overweight). The mean neck circumference for men is 38.5 cm (Large), for women is 37.1 cm (Large), and based on the neck circumference cut-off point, classified as Obesity Level I. The average of skinfold thickness is 23.6 mm for men and 18.4 mm for women. The average body fat percentage for men is 23.5% (Fat), and for women is 27.5% (Slightly Overfat). Spearman correlation test showed a significant relationship between neck circumference and skinfold thickness on body mass index (p<0,05) with a strong correlation on neck circumference (r=0.526) and a very strong correlation on skinfold thickness (r=0.837), and the direction of correlation is in the same direction (positive). There is a significant relationship between neck circumference and skinfold thickness on body mass index.